(untitled) (Research, Society and Development, 2021)
The aim of this study is the macroscopic environmental assessment of the springs and their permanent preservation areas and the bed located in the basin of the Corrente do Matões stream. The study was conducted in the basin of the Corrente dos Matões stream, where field trips were carried out in order to assess the vegetation, environmental impacts, geological aspects, characterization of the permanent preservation area associated with the spring, direct access to animals, presence of household waste in the springs and surroundings, constructions, water collection, multiple uses, proximity to impacting activities, in addition to other aspects that were noted and recorded with a camera and a GPS. Collections of water samples were also carried out to assess the concentration of some chemical elements. In view of the analysis of this study, it was registered that the Riacho Corrente dos Matões has five springs, being fed only by three. The study also revealed that, depending on the use of the land, the impacts are different in the basin of the Corrente dos Matões stream and that, even though it is a river located in the rural area, it suffers pressure with the advance of urbanization.